2008
DOI: 10.1002/gamm.200890010
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanically coupled modelling of shape memory alloys in the framework of large strains

Abstract: In the present work we propose a new thermomechanically coupled material model for shape memory alloys (SMA) which includes the two main effects observed for these materials, pseudoelasticity and the shape memory effect. The constitutive equations are derived in the framework of large strains since the martensitic phase transformation involves inelastic deformations up to 10%, or even up to 20% if the plastic deformation after the phase transformation is taken into account. Therefore we apply a multiplicative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In literature it is referred to as driving force ( [22,23]) or thermodynamic force ( [20,21]), for further explanation see Sect. 2.4.…”
Section: Constitutive Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In literature it is referred to as driving force ( [22,23]) or thermodynamic force ( [20,21]), for further explanation see Sect. 2.4.…”
Section: Constitutive Equationsmentioning
confidence: 99%
“…The finite element implementation considers pseudoelasticity. Christ and Reese [22][23][24] enhance the work for pseudoplasticity and the shape memory effect. An overview on existent models, their numerical treatment and further research topics on shape memory alloys may be found in Lagoudas [25].…”
Section: Introductionmentioning
confidence: 99%
“…In literature it is referred to as driving force ( [8], [9]) or thermodynamic force ( [14], [15]), for further explanation see section 2.4.…”
Section: Constitutive Equationsmentioning
confidence: 99%
“…The finite element implementation was done for pseudoelasticity. Christ and Reese [8], [9], [10] improve the model of Helm and Haupt. They implement each material phenomenon into the finite element method.…”
Section: Introductionmentioning
confidence: 99%